Structural and Optothermal Properties of Iron Ditelluride Layered Structures in the Framework of the Lattice Compatibility Theory - K. Ben Messaoud; A. Gantassi; H. Essaidi; J. Ouerfelli; A. Colantoni; K. Boubaker; M. Amlouk (Advances in Materials Science and Engineering)
This study concerns structural and optothermal properties of iron ditelluride layered structures which were fabricated via a low-cost protocol. The main precursors were FeCl3 · 6H2O and Fe2O3. After a heat treatment within a tellurium-rich medium at various temperatures (470°C, 500°C, and 530°C) during 24 h, classical analyses have been applied to the iron ditelluride layered structures. A good crystalline state with a preferential orientation of the crystallites along (111) direction has been recorded. Moreover, additional opto-thermal investigation and analyses within the framework of the Lattice Compatibility Theory gave plausible explanation for prompt temperature-dependent incorporation of tellurium element inside hematite elaborated matrices.